Hemoglobin Rahere, a human hemoglobin variant with amino acid substitution at the 2,3-diphosphoglycerate binding site. Functional consequences of the alteration and effects of bezafibrate on the oxygen bindings. - Sugihara, J (1985)
We encountered an abnormal hemoglobin (Rahere), with a threonine residue replacing the beta 82 (EF6) lysine residue at the binding site of 2,3-diphosphoglycerate, which was responsible for overt erythrocytosis in two individuals of a Japanese family. Hemoglobin Rahere shows a lower oxygen affinity on the binding of 2,3-diphosphoglycerate or chloride ions than hemoglobin A. Although a decrease in the positive charge density at the binding sites of 2,3-diphosphoglycerate in hemoglobin Rahere apparently shifts the allosteric equilibrium toward the low affinity state, it greatly diminishes the cofactor effects by anions. The oxygen affinity of the patient's erythrocytes is substantially lowered by the presence of bezafibrate, which combines with sites different from those of 2,3-diphosphoglycerate in either hemoglobin Rahere or hemoglobin A.